Use of time‐resolved spectroscopy as a method to monitor carotenoids present in tomato extract obtained using ultrasound treatment. Issue 1 (20th August 2015) - Bot, Francesca; Anese, Monica; Lemos, M. Adília; Hungerford, Graham
Abstract: Introduction: Compounds exhibiting antioxidant activity have received much interest in the food industry because of their potential health benefits. Carotenoids such as lycopene, which in the human diet mainly derives from tomatoes ( Solanum lycopersicum ), have attracted much attention in this aspect and the study of their extraction, processing and storage procedures is of importance. Optical techniques potentially offer advantageous non‐invasive and specific methods to monitor them. Objectives: To obtain both fluorescence and Raman information to ascertain if ultrasound assisted extraction from tomato pulp has a detrimental effect on lycopene. Method: Use of time‐resolved fluorescence spectroscopy to monitor carotenoids in a hexane extract obtained from tomato pulp with application of ultrasound treatment (583 kHz). The resultant spectra were a combination of scattering and fluorescence. Because of their different timescales, decay associated spectra could be used to separate fluorescence and Raman information. This simultaneous acquisition of two complementary techniques was coupled with a very high time‐resolution fluorescence lifetime measurement of the lycopene. Results: Spectroscopic data showed the presence of phytofluene and chlorophyll in addition to lycopene in the tomato extract. The time‐resolved spectral measurement containing both fluorescence and Raman data, coupled with high resolution time‐resolved measurements, where a lifetime of 5 ps was attributed to lycopene, indicated lycopene appeared unaltered by ultrasound treatment. Detrimental changes were, however, observed in both chlorophyll and phytofluene contributions. Conclusion: Extracted lycopene appeared unaffected by ultrasound treatment, while other constituents (chlorophyll and phytofluene) were degraded. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Carotenoids, such as lycopene, are of interest to the food industry because of potential health benefits from their antioxidant activity. Time‐resolved spectroscopy was employed to simultaneously obtain fluorescence and Raman information. These measurements, along with a high time‐resolution fluorescence lifetime measurement, were used to monitor the effect of ultrasound treatment to assist extraction of lycopene from tomato pulp. The lycopene was found to be unaffected by ultrasound treatment, but other constituents (principally chlorophyll and phytofluene) were degraded.